(untitled) - Winters, Cat (New York, 2014)
In 1918, the world seems on the verge of apocalypse. Americans roam the streets in gauze masks to ward off the deadly Spanish influenza, and the government ships young men to the front lines of a brutal war, creating an atmosphere of fear and confusion. Sixteen-year-old Mary Shelley Black watches as desperate mourners flock to séances and spirit photographers for comfort, but she herself has never believed in ghosts. At her bleakest moment, however, she’s forced to rethink her entire way of looking at life and death, for her first love—a boy who died in battle—returns in spirit form. But what does he want from her?Featuring haunting archival early-20th-century photographs, this is a tense, romantic story set in a past that is eerily like our own time.
Keywords: World War, 1914-1918,Ma quỷ,Chiến tranh thế giới, 1914-1918,Ghosts; Fiction,Tiểu thuyết,Tiểu thuyết,Fiction